Analisis Unsur Teks Berita Mahasiswa Magang - Aisah Aisah; Desi Sukenti (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
Writing news with the application of the 5W+1H elements is the main requirement that must be applied to get good and appropriate news writing, as can be seen from the phenomena that there are still some errors in news writing in the application of the 5W+1H elements in student internship reports. The purpose of this study is to describe, analyze and interpret the analysis of news elements in terms of what and where application in the student intern reports on the Radar Riau daily newspaper. The theory used is the 5W+1H formula in Djuraid's 2012 and Chaer's 2010 books. This type of qualitative research and literature with this research method is content analysis or content analysis. The source of the data in this study was the student intern report in the Radar Riau daily newspaper. The results of this research are reports of Internship Students at the Radar Riau Public Daily Newspaper that have applied the what formula in news writing, and the way of writing and applying it is correct according to the existing theory, namely what happened, lies in the news title. Reports of Internship Students at the Radar Riau General Daily Newspaper, there are still some perfectly clear implementations of the where formula in news writing, namely 6 data is quite good and clear, and 6 other data is still incomplete. Writing news elements where and its application is not completely correct according to theory, namely the place of occurrence or events.